Acoustic signatures of organic films floating on the sea surface - POGORZELSKI, S. J. (Archives of Acoustics, 1994)
A spectrum of low-frequency amplitude fluctuations of the ultrasonic signal specularly scattered from a wind-driven water surface covered with monomolecular crude oil origin film of well-defined oceanographically relevant viscoelastic properties, was examined in open-sea conditions. The depression of the spectral energy density of wind-created waves by surface films is inferred from the spectra ratio of the acoustic signal fluctuations spectra with/without films, and compared to that predicted by the Marangoni damping theory. Theoretical computations showed that the film filling factor determined for natural sea surface films in coastal waters of the Baltic Sea plays a principal role in determination of the film rheological properties recovered from the acoustic surface probing, whereas a variation of the growth rate of wind waves affected by the film presence is of secondary importance. It has been demonstrated that the relative spectra can be analyzed to characterize the viscoelastic properties of surface films, which for a gasoline film-coated surface turned out to be comparable to these of natural slicks or weathered crude oil spills.